Performance of STAR virtual trials for diabetic and non-diabetic in HTAA intensive care unit - Jamaludin U.K.; Dzaharudin F.; Razak N.N.A.; Luqman H.M.; Zulkifly W.Z.W.M.; Suhaimi F.M.; Ralib A.M.; Nor M.B.M.; Pretty C.G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomedical engineering; Blood; Diseases; Glucose; Insulin; Intensive care units; Medical problems; Stars; Stochastic control systems; Stochastic models; Stochastic systems; Blood glucose; Blood glucose controls; Blood glucose management; Critically-ill patients; Insulin sensitivity; Intensive care; Intensive insulin therapies; virtual trial; Patient treatment